IDENTIFYING COMPETENCE STATUS OF DEANS AND DEPUTIES OF ISLAMIC AZAD UNIVERSITY - Khanghahi, Mahshad; Bahramzade, Hosein (Revista Inclusiones, 2019)
This study aimed at identifying the competence of deans and deputies of the faculty members of Islamic Azad University. It was an applied, quantitative and non-experimental research. The statistical population included all the full-time faculty members of Islamic Azad University of Khorasan Razavi with a total population of 508, and the sample size was calculated using the Cochran formula to be 219 people. The simple random sampling was used in this study as the statistical population was homogeneous. After library search and interviewing experts and identifying factors affecting the competence of deans and deputies of the Islamic Azad University, a conceptual model was designed and evaluated through a questionnaire. Validity of the questionnaire was verified through content and construct validities and reliability using Cronbach alpha coefficient and composite reliability (CR) which were above 0.7. One-sample T-test was used to investigate the status of the variables. The results showed that the status of variables related to communication-human, perceptual, management, professional-expert, belief and value factors were favorable among the deans and deputies of Islamic Azad University.